Морфонологія словотвірних гнізд, вершини яких закінчуються на -б(ий), -п(ий), -в(ий), -м(ий) - Пристай, Галина; Prystai, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано словотвірні гнізда прикметників з погляду морфонології: схарактеризовано структуру вершинних основ, особливості будови поєднуваних з ними дериваційних суфіксальних морфем, описано морфонологічні операції, укладено основні морфонологічні моделі.The article deals with the analysis of the adjectival derivatives of the point of view of morphonology. It describes the morpheme structure of the analyzed derivational stems and suffixes, distinguishes the morphonological modifications within the word building nests. The major task of this study is to set the peculiarities of morphonological manifestation patterns in the specified derivational nests. In general, this research shows that the morphonological structure of a derivational nest depends on the peculiarities of the morphonological structure of a root morpheme. The data clarify the main morphonological operation in the studied nests – palatalization, in particular the transition of labial palatalization. The operations of stress alternation (from the base / suffix to suffix / flexion / basis) in this morphonological type of nests are also characterized by relatively high activity. Morphonological transformations are summarized by creating basic morphonological models.
Morphonology of Derivational Nests With the Top Adjectives Ending -b(yy), -p(yy), -v(yy), -m(yy)
Keywords: морфонема; контактна зона; ступінь похідності; чергування; палаталізація; акцент; morpheme; contact zone; the degree of derivation; alternation; palatalization; accent